Prosperity: A new and foreign element in African Christianity - Gifford, Paul (Religion, 1990)
African Christianity is currently characterized by an evangelical revival which is in large measure funded and directed from California and the southern United States. Through these connections, North American Christianity is having considerable influence on a large segment of African Christianity. This article outlines one US development called ‘The Gospel of Prosperity’, and examines its spread to Africa. The author argues that this Gospel of Prosperity has particular socio-political effects; this form of Christianity provides no incentive to economic analysis and socio-political involvement, and thus accentuates further the differences between African Christianity and the liberation theology of Latin America.
paid